KONTRIBUSI TUJUH NILAI-NILAI WASIAT LUQMAN HAKIM DALAM Q.S. LUQMAN AYAT 13-18 TERHADAP PSIKOLOGI PERKEMBANGAN ANAK USIA DINI: Studi Analisis Tentang Psikologi Perkembangan Anak Usia Dini - Nur Hilwa Layyina (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
In the development of life requires materials to achieve success. This calmness will crystallize into the coveted happiness in every human being. From this background, the author wants to give a view, the ingredients needed to achieve happiness that have different wheel-control but have the same focus. In this thesis, the author focuses on the seven wills of Luqman Hakim in order to contribute to the development of the psychology of early childhood development. The seven wills of Luqman Hakim, the authors discussed, among others; first; Forgive God Almighty, second; Do good to both parents, third; No matter how small the good is definitely returned, fourth; Working on prayer, fifth; Amal makruf nahi mungkar, sixth Patient for all trials and seventh Not arrogant. Of the seven testaments, it is able to give the doctrine that these testaments are capable of forming positive characters from the world to the hereafter and are able to strengthen positive relations between humans and their gods. From this design, at least seven testaments of Luqman Hakim are able to contribute to the formation of character for early childhood. As for some of the contributions, among others, first; The formation of religious personal character towards early childhood, second; Formation of personal character responsible for early childhood, third; Establishment of a character of confidence in early childhood, fourth; Formation of the character of independence for early childhood, fifth; Formation of the character of self-awareness towards early childhood, sixth; Formation of personal character that is patient towards early childhood, seventh; Tawadhu ’character formation for early childhood. From some of these contributions, the main conclusions in this thesis are in the contribution of Luqman Hakim's will in the formation of character in early childhood. From some of the descriptions, has a conclution that Luqman Hakim's will listed in the text of the Qur'an is able to contribute in the real world. And if we are able to instill these messages, undoubtedly the formation of the pious character of the child and the acrom we can feel in this life. From this starting point, we can realize the hope of building a peaceful, peaceful and happy life.